The role of the stratigraphic on quantity and quality water karst springs In Shotori mountains, west Tabas - Hassan Zia; Gholamhossein Karami; Ali Taheri (Journal of Stratigraphy and Sedimentology Researches, 2017)
The Shotori Mountains, with an area of about 2500 Km2 are located in west Tabas. Carbonate formations outcrops are about 53% and include Gamal, Shotori and Esfandiar formations. Sequence stratigraphy and difference hydrostratigraphy leaded to forming three karstic aquifers entitled Gamal, Shotori and Esfandiar. Almost all springs in this studied area emerge from these karst formations. So that annual discharge these karst springs is about 83% of total annual discharge in the studied area. The higher extend, thick layer and more purity of the limestone in Esfandiar formation in comparison with the Gamal and Shotori formations lead to the higher degree of karstification in this formation so that the main springs emerging from this formation. In addition to the effect of stratigraphy on quantity, it has a significant effect on the quality of the discharging water from the springs in the area. Springs which discharge form Esfandiar formation with volcanic and Qala Dokhtar formation basement have higher quality than Esfandiar with Baghamshah basement. The electrical conductivity of the first group of springs is below 500 µS/ cm whereas it fluctuates between 700 to 1800 µS/ cm in the second group.